EFFECT OF NUTRIENT MANAGEMENT ON GROWTH, YIELD AND QUALITY OF SUMMER MUNGBEAN ( ALITY OF SUMMER MUNGBEAN (VIGNA RADIATA L.) - BANSAL, MONU; AHMAD, ANJUM (The Bioscan, 2016)
A field experiment was conducted during summer season of 2012 at Muzaffarpur. Result revealed that Growth attributes were significantly higher found under application of 100 % RDF, 50% RDF + 2 % urea spray at 40 DAS. HW at 25 DAS and pendimethalin @ 1.0 kg ai ha-1 increased all the growth and yield attributes. Highest grain yield obtained under 100% RDF 12.60 q ha-1. HW at 25 DAS recorded max. grain yield 13.50 q ha-1 being at par with PE pendimethalin @ 1 kg ai ha-1 12.67 q ha-1. Thus it can be concluded that application of 100% RDF and HW at 25 DAS proved to be better nutrient and weed management practice over other practices.